The information agenda of the Turkic World in the media space of the Central Asian region (Herald of Journalism, 2022)
The article is devoted to the study of the basic parameters of the media space of the Central Asian region in the thematic segment "Turkic world" and the information agenda. The need for research is due to the fact that integration processes are growing between the Turkic-speaking countries.The purpose of the study is to identify the main informational occasions for the media that characterize the reflection of the problems of Turkic studies and the Turkic world in the media space of the countries of Central Asia. Research methods: analysis and synthesis, monitoring and content analysis of the media.The results of the study showed that the published messages in the segment of the media space are more related to political issues. At the same time, it is the media space that is a kind of "repository" of the history, culture, traditions of the Turkic-Slavic peoples, and the media perform the function of cultural reproduction in modern society.The scientific significance of the results of the study lies in the fact that for the first time an assessment of the key parameters of the media space in the thematic segment “Turkic world” was made (the number of publications, the proportion of originals/reprints, information occasions, categories, branches; mass media by genres, headings, by authors). The results of the analysis make it possible to characterize the main media trends in the coverage of key events in the Turkic world, to identify the most influential media that form public opinion. The practical significance is determined by the fact that on the basis of the obtained data it is possible to build an optimal communication strategy for organizations that study the problems of Turkic studies and the Turkic world.Keywords: mass media, media space, Turkic world, information agenda, communications, media analysis.